Pelatihan Pengelolaan Konflik Organisasi Akibat Media Sosial Bagi Karang Taruna di Desa Ciburial, Bandung - Ditha Prasanti; Sri Seti Indriani (Jurnal Pengabdian Pada Masyarakat, 2018)
TRAINING OF ORGANIZATIONAL CONFLICT MANAGEMENT DUE TO SOCIAL MEDIA FOR YOUTH CADETS IN CIBURIAL VILLAGE, BANDUNG. This article is the result of Community Service Activity (PKM) which has been done by the writer team on Karang Taruna members in Ciburial village, Bandung, under the title of Managing Organizational Conflict Managing Social Media Training for Karang Taruna of “Padu Selaras” in Ciburial Village. Community Service Activities has the objective of producing outcomes: 1) Providing concrete knowledge on how to manage organizational conflicts caused by social media; 2) Provide an understanding of the importance of members of youth have knowledge of the management of organizational conflict caused by social media. The method of PKM implementation done in this activity is method of lecture method; group discussion methods; and video playback methods. The conclusions of this PKM activity are: 1) To awaken members of youths about the importance of having knowledge in managing organizational conflicts caused by social media; 2) Increasing the knowledge of youth members about conflict management caused by social media; 3) Practicing how to manage organizational conflict due to social media in simulation of members of youth cadets in Ciburial village.